The Impact of Loan Products, Promotion, Service Quality, and Location Regarding Customer Decisions on People’s Business Credit Loans (KUR) PT BRI UNIT MERUYA ILIR - Setiasih; Ida Adhani; Muhammad Iqbal (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2024)
This study attempts to examine the impact of loan products, promotions, quality of service, and location on choices made by customers on PT Bank Rakyat Indonesia Unit Meruya Ilir People's Business Credit (KUR) loans. Multiple linear regression analysis with coefficient of determination analysis is the data analysis technique employed (adjusted R square), t test, and F test using a sample of 87 respondents. The results of data processing from linearof multiple regression analysis produce the equation Y=5.732 + 0.085X1 + 0.503X2 + 0.155X3 + 0.327X4. The test of the coefficient of determination test acquired a modified R square value of 0.617, or 61.7%, meaning that customer decisions are explained by loan products, promotions, service quality, and location of 61.7%. The test of the t test explain that the loan product variable has no partial effect on customer decisions,theof variable promotion has a partial effect on customer decisions . The quality of service variable has no partial effect on customer decisions. The location variable partially influences customer decisions . The test of F show an Fcount value of 35.634 > Ftable 2.48 and a Sig value of 0.000 < 0.05. This indicates that there is a concurrent impact between loan products, promotions, quality of service, and location on customer decisions on PT Bank Rakyat Indonesia's Meruya Ilir unit People's Business Credit (KUR) loans.